Composition control of YbFe2O4 electronic ferroelectric thin films with PLD growth process monitoring - K. Shimamoto; T. Hayama; T. Yoshimura; N. Fujimura (APL Materials)
RFe2O4 is expected to deliver high-performance ferroelectricity that can reduce the fatigue associated with polarization reversal and the electric field (coercive field) required for polarization switching because its ferroelectricity originates from charge ordering. However, there have been very few reports on the fabrication of thin films of the material because of the severe growth condition of an extremely reduced oxygen atmosphere, even though the material is an oxide. To provide cutting-edge insights into elucidating the essential fundamental properties of thin films of RFe2O4, we developed a reproductive fabrication method to control both the phase formation and composition of YbFe2O4 epitaxial thin films. We investigated principles guiding the fabrication of the YbFe2O4 epitaxial thin films with a customized pulsed laser deposition (PLD) system. The optimal laser fluence for crystal growth was controlled by tuning the laser energy and focusing lens position, assisted by an in situ monitoring technique of the plasma plume ablated from the ceramic target with optical emission spectroscopy. A multiple-target PLD system using six varieties of ceramic targets with different crystal phases and compositions was introduced to control the Fe/Yb composition ratio of YbFe2O4 epitaxial thin films. Combining these techniques paves the way for overcoming the stoichiometric issues in this series of crystal structures toward novel device applications.